The guidance services in Pasay City high schools as perceived by students, teachers, administrators and guidance counselors - Sayo, Teresita P. (Capili) 1932- (1974)
This study measured the extent of the procedural implementation of the guidance services recommended by the Bureau of Public Schools as perceived by senior students, homeroom advisers, administrators and counselors.
Thesis (M.Ed.)--University of the Philippines
Keywords: Personnel service in education -- Philippines; Counseling